Orlando Dugi speaking to class - Unidentified photographer (Colorado State University. Libraries, 2019)
Photograph of designer Orlando Dugi speaking about his design inspiration to a class in 2019. Dugi is standing next to a projector screen with students seated in the foreground.
Keywords: Fashion -- History; Fashion -- Exhibitions